DIAGNÓSTICO MOLECULAR DO SARS-COV-2 E ANÁLISE DAS CARACTERÍSTICAS EPIDEMIOLÓGICAS OBSERVADAS NO OESTE DO PARANÁ - Candido, Kattlyn Laryssa (2022)
The coronavirus pandemic has become a massive problem in recent years, with over 650,000 deaths in Brazil, and more than 550 mi of people have been infected with COVID-19 globally. In this situation, the Molecular Biochemistry Laboratory (LaBioqMol) of UNIOESTE started to diagnose the disease through real time qRT–PCR, the gold-standard diagnostic method for COVID-19. Furthermore, our goal was to analyze the epidemiological characteristics of the diagnosed patients in our service and to better understand the structural characteristics of the SARS CoV-2 spike (S) protein. The samples collected through nasopharyngeal swabs were analyzed and processed using real-time qRT–PCR targeting SARS-CoV-2 genetic material. The patients also completed a notification form, which was used to notify the patient of the vigilance programs and compile epidemiological data to be further analyzed. A total of 238 community patients attended our service on demand, and the median age was 35,11±14,46, mostly women (57,62%). The age group mostly seen in LaBioqMol was 20 to 29 years (31,93%). The genetic material of the virus was detected in 79 subjects (33,19%). The median time between the sampling and the results delivery was 0,07 days with a standard deviation of ± 0,25; thus, most of our patients received their results within the day of sampling. Additionally, most of them worked in the commercial sector (32,91%) and lived in the southern region of Cascavel (30,38%). In parallel, the structural study of the S protein resulted in a review of its mutations and the new viral variants and didactic figures related to the viral cycle and 3 tables compiling the available data about Omicron’s S protein mutations. Further than thar, we conducted a screening for SARS-CoV-2 immunoglobulins in 123 subjects of Santa Tereza, comparing with RT-PCR results and vaccination data. We concluded that the rapid test used were not sensible enough e that should not be used as a diagnostic tool in these settings. The execution of this project allowed not only the significant contribution to managing contaminated people during the COVID-19 pandemic in Cascavel from October/20 to September/21 but also the better understanding and scientific production of the new coronavirus and its variants.